IFRS Transition in The Republic of Uzbekistan: An Analytical ‎Perspective on PP&E Impairment - Artemenkov, Andrey; Nandy, Monomita; Azamov , Jobir; Ganiev, Omonjon; Kumar, Amil (International Journal of Accounting and Economics Studies, 2025)
This study examines asset revaluation and impairment under International Financial Reporting ‎Standards (IFRS), with a focus on Uzbekistan's first-time adoption. Specifically, it focuses on the ‎implementation of first-time value-in-use-based impairment tests for PP&E assets. ‎To address the development gap for highly-granular automated impairment and reversal algo‎rithms identified in the accounting operations literature, we develop a dynamic discrete-period ‎technique for impairment and reversal transformations of assets’ costs that efficiently discrimi‎nates for the commissionings and disposals in PP&E inventory over the standard two-year IFRS ‎transition period. The case study application of this algorithm finds evidence to indicate successful-performing automated impairment and reversal allocations at the level of individual ‎PP&E assets in the stress-test-like context of Covid-era-associated high volatilities in values-in-use for the transitioning entity. It is shown that the proposed algorithm effectively safeguards against the over-reversal of impairments, ensuring full compliance with IAS 36’s paragraph 117 requirements.‎‎ The findings will extend the accounting literature related to developing impairment and reversal ‎algorithms of high granularity. In practical terms, the findings will also contribute to the literature ‎on first-time IFRS adoption by highlighting the intricacies of asset revaluation and impairment in ‎IFRS transitional contexts confronted by developing countries, specifically Uzbekistan’s unique ‎IFRS transitional context, wherein large state-controlled entities underwent IFRS transition amid ‎the COVID pandemic, necessitating drastic initial impairments followed by partial reversals as ‎economic conditions improved. The description of this experience can be of value in similar ‎transitional contexts‎.
Keywords: IFRS Adoption; Impairment Tests; Impairment Reversal, Value in Use; Cash-Generating Unit; Uzbekistan; IAS 36‎